Exploring the Preliminary Effects of Resistance Training on Total Brain-Derived Neurotrophic Factor (BDNF) Levels in Elderly Individuals: A Pilot Study (Baltic Journal of Sport and Health Sciences, 2023)
Background: Studies have shown that exercise modulates brain-derived neurotrophic factor (BDNF) levels, and resistance training, in particular, has received increasing attention for its potential to enhance BDNF production. Most studies investigating exercise-induced BDNF changes have focused on free or mature BDNF, while the measurement of total BDNF, encompassing both proBDNF and mature BDNF, may provide a more comprehensive understanding of BDNF regulation. This pilot study aimed to explore the preliminary effects of resistance training on total BDNF levels in elderly individuals participating in a resistance training program.Methods: A small sample of participants (n=6) was recruited and engaged in a structured resistance training program for 12 weeks, with 6 participants in a control group. Total BDNF levels were measured at baseline and post-intervention using reliable laboratory assessments. Additionally, an isokinetic dynamometer was used to determine muscle strength to explore the effect of the resistance training program on muscle performance.Results: The findings revealed a significant increase in total BDNF levels following the 12 week resistance training intervention (p